2013
DOI: 10.3384/confero.2001-4562.13v1i21g
|View full text |Cite
|
Sign up to set email alerts
|

Queering School, queers in school

Abstract: Queer studies of education have become a growing field with a range of theoretical and political positions and methodological approaches. Moreover, research with lesbian, gay, bisexual, transgender and queer (LGBTQ) kids is tightly connected to anti-homophobia, anti-transphobia and norm-critical activism. One of the key contentions within this field is what researchers and activists mean by “queer” in the context of education: is it a focus on queer/ed subjectivities? Is it about using queer theories to critiq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Our education worlds, so heavily bounded and surveilled (Foucault, 1991), are clear beneficiaries of such queer, norm-exploding potential. We can observe queer pedagogy’s definitional defiance and its earlier cited ‘stubborn vitality’ in the rich, contextually divergent examples of queer doings in education in schools, higher education and within the community (Britzman, 1998; Cavanagh, 2008; Malmquist et al, 2013; Shalsko, 2005; Whitlock, 2010). Indeed, Harris and Farrington tell us that:Queerness has well and truly moved into classrooms, in ways that are sometimes hopeful, sometimes crushing, but always unruly … whether these moves are on the part of teachers … or of students, queer and its complexities are now visible and vocal in many schools across the globe.…”
Section: Queer–feminist Pedagogymentioning
confidence: 97%
See 1 more Smart Citation
“…Our education worlds, so heavily bounded and surveilled (Foucault, 1991), are clear beneficiaries of such queer, norm-exploding potential. We can observe queer pedagogy’s definitional defiance and its earlier cited ‘stubborn vitality’ in the rich, contextually divergent examples of queer doings in education in schools, higher education and within the community (Britzman, 1998; Cavanagh, 2008; Malmquist et al, 2013; Shalsko, 2005; Whitlock, 2010). Indeed, Harris and Farrington tell us that:Queerness has well and truly moved into classrooms, in ways that are sometimes hopeful, sometimes crushing, but always unruly … whether these moves are on the part of teachers … or of students, queer and its complexities are now visible and vocal in many schools across the globe.…”
Section: Queer–feminist Pedagogymentioning
confidence: 97%
“…2010: 7Our education worlds, so heavily bounded and surveilled (Foucault, 1991), are clear beneficiaries of such queer, norm-exploding potential. We can observe queer pedagogy's definitional defiance and its earlier cited 'stubborn vitality' in the rich, contextually divergent examples of queer doings in education in schools, higher education and within the community (Britzman, 1998;Cavanagh, 2008;Malmquist et al, 2013;Shalsko, 2005;Whitlock, 2010). Indeed, Harris and Farrington tell us that:…”
Section: Queer-feminist Pedagogymentioning
confidence: 99%
“…Sexual identities have also become distinctly visible in religious contexts, with the proliferation of gay-affirmative Christian congregations (Kane, 2013). Schools have begun to recognize the need for ''queering'' their institutions through creating a ''safe space'' for young gay persons to self-identify along a spectrum of gender and sexuality (Malmquist et al, 2013). The affiliation of sexuality with political, social, and economic institutions has ensured that sexuality remains visible, contested, and is asserted through categorical identities.…”
Section: Competing Sexual Schemasmentioning
confidence: 99%
“…Studies carried out within the Swedish educational context have shown how heteronormativity is in play in different educational settings (Ambjörnsson, 2004;Bäckman, 2003Bäckman, /2006Bengtsson, 2013;Bromseth, 2009) as well as in language education (Ericsson, 2015;Jonsson, 2007;Milani & Jonsson, 2011). However, there is a call for more research on processes that bring about subjectivity in school (Malmqvist, Gustavson, & Schmitt, 2013). This is pertinent not least in Swedish language education, which has been emphasized as an area in need of more research generally (Lindgren & Enever, 2015, p. 12).…”
Section: Introductionmentioning
confidence: 99%